1997
DOI: 10.3109/09637489709006958
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Effects of Energy Intake at Breakfast on the Test Performance of 10-Year-Old Children in School

Abstract: In order to examine the effect of energy intake at breakfast on school performance the same morning, the parents of ten parallel school classes of 10-year-old school children at five different schools were persuaded to alter their child's breakfast regimen at home over a period of 4 successive days. A total of 195 families were provided with standard breakfasts with either low or high energy content. Uneaten food was returned and weighed. Individual children were randomly assigned to breakfast alternative on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 10 publications
3
74
0
1
Order By: Relevance
“…In before-lunch physical endurance tests among 10-year-old children, those consuming a breakfast that provided over 20 % of their estimated daily energy requirement performed significantly better than those consuming a breakfast that provided only 10 % of the requirement (18) . Furthermore, Vermorel et al illustrated that the consumption of an inadequate breakfast does not meet the energy expenditure requirements of adolescents participating in morning physical activity sessions at school (19) .…”
mentioning
confidence: 85%
“…In before-lunch physical endurance tests among 10-year-old children, those consuming a breakfast that provided over 20 % of their estimated daily energy requirement performed significantly better than those consuming a breakfast that provided only 10 % of the requirement (18) . Furthermore, Vermorel et al illustrated that the consumption of an inadequate breakfast does not meet the energy expenditure requirements of adolescents participating in morning physical activity sessions at school (19) .…”
mentioning
confidence: 85%
“…(Though, some studies have not found effects on specific attention, memory and mood measures, Cromer et al, 1990;Smith et al, 1994;Benton et al, 2001) These findings are borne out by experimental studies conducted in school settings, which have shown positive effects of breakfast on memory (Vaisman et al, 1996), arithmetic (Powell et al, 1998), verbal fluency (Chandler et al, 1995), physical endurance, creativity (Wyon et al, 1997) and on-task behaviour (Bro et al, 1994). In a review of this literature, Pollitt (1995) concluded that breakfast consumption consistently improves the cognitive performance of undernourished children and, in the United States and Great Britain, also has cognitive benefits for well-nourished children.…”
mentioning
confidence: 99%
“…It would also appear that the quantity and quality of breakfast influences the performance of school-age children (Pollitt et al, 1982;Vaisman et al, 1996;Owens et al, 1997). For example, in Sweden, 10-y-olds who took more abundant breakfasts were those who performed best in morning gym classes and in verbal fluidity tests (Wyon et al, 1997). One mechanism that might explain these benefits is the increase in blood glucose after having such a meal (Benton & Sargent, 1992;Benton & Parker, 1998;Benton et al, 2001).…”
Section: Discussionmentioning
confidence: 99%